Gypsophila munzurensis (Caryophyllaceae), a new species from Tunceli (Turkey) - Armagan, Metin (Phytotaxa, 2016)
A new annual species belonging to the genus Gypsophila sect. Hagenia—G. munzurensis—is here described and compared with the similar G. pilosa as part of the study of the flora of Tunceli (Turkey). G. munzurensis differs from G. pilosa by its shape of the leaves and petals, indumentum of stem, pedicel and calyx. A detailed description, and original photographs are provided as well as the current distribution area and the conservation status are also discussed.